Applying Advanced Imaging Techniques to a Murine Model of Orthotopic Osteosarcoma - Broadhead, Matthew L.; Lokmic, Zerina; Tan, Mei Lin; Stevenson, Andrew; Binns, David S.; Cullinane, Carleen; Hicks, Rodney J.; Choong, Peter F. M.; Myers, Damian E. (Frontiers in Surgery, 2015)
Introduction Reliable animal models are required to evaluate novel treatments for osteosarcoma. In this study, the aim was to implement advanced imaging techniques in a murine model of orthotopic osteosarcoma to improve disease modeling and the assessment of primary and metastatic disease. Materials and methods Intra-tibial injection of luciferase-tagged OPGR80 murine osteosarcoma cells was performed in Balb/c nude mice. Treatment agent (pigment epithelium-derived factor; PEDF) was delivered to the peritoneal cavity. Primary tumors and metastases were evaluated by in vivo bioluminescent assays, micro-computed tomography, [18F]-Fluoride-PET and [18F]-FDG-PET. Results [18F]-Fluoride-PET was more sensitive than [18F]-FDG-PET for detecting early disease. Both [18F]-Fluoride-PET and [18F]-FDG-PET showed progressive disease in the model, with 4-fold and 2-fold increases in SUV (p<0.05) by the study endpoint, respectively. In vivo bioluminescent assay showed that systemically delivered PEDF inhibited growth of primary osteosarcoma. Discussion Application of [18F]-Fluoride-PET and [18F]-FDG-PET to an established murine model of orthotopic osteosarcoma has improved the assessment of disease. The use of targeted imaging should prove beneficial for the evaluation of new approaches to osteosarcoma therapy.